A nondestructive approach to predict buckling load of composite lattice-core sandwich conical shells based on vibration correlation technique. (November 2022) - Zarei, Mehdi; Rahimi, Gholamhossein H
In this paper the vibration correlation technique (VCT) has been used as a nondestructive method for predicting the buckling load of the composite lattice-core sandwich conical shells. This technique is capable of predicting the buckling load of different structures without reaching the failure point through modal testing. The composite lattice-core sandwich conical shell has been fabricated using a filament winding process. To perform the expriment, the fundamental natural frequency of the specimen is measured under stepped axial compression loading. The procedure is followed up without actually reaching the instability point when the structure collapses and is no longer usable. A finite element model has also been built in ABAQUS in order to determine the correlation between natural frequency and applied compressive load. A comparison of the results indicated that the VCT has provided a reliable estimate of the buckling load of composite lattice-core sandwich conical shells, especially when the structure is loaded up to at least 66% of the experimental buckling load and accuracy of the VCT decreases when the maximum load is lower than 43% of the buckling load. Results also revealed that the linear fitted curve is unsuitable for the correlation between frequency of vibration and applied load in order to predict buckling load.